2012
DOI: 10.1371/journal.pone.0050559
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment with Allopurinol or Uricase Attenuates Barrier Dysfunction but Not Inflammation during Murine Ventilator-Induced Lung Injury

Abstract: IntroductionUric acid released from injured tissue is considered a major endogenous danger signal and local instillation of uric acid crystals induces acute lung inflammation via activation of the NLRP3 inflammasome. Ventilator-induced lung injury (VILI) is mediated by the NLRP3 inflammasome and increased uric acid levels in lung lavage fluid are reported. We studied levels in human lung injury and the contribution of uric acid in experimental VILI.MethodsUric acid levels in lung lavage fluid of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…They also showed that local administration of exogenous UA crystals recapitulates lung inflammation and repair. Local UA levels are also increased in patients with ALI, a syndrome characterized by the accumulation of neutrophils in the lung accompanied by the development of interstitial edema and an intense inflammatory response [23] . In fact, neutrophils rapidly infiltrate the pulmonary parenchyma after hypovolemic shock, intestinal ischemia/reperfusion, or endotoxin administration [8] , while the depletion of neutrophils reduces pulmonary edema and proinflammatory cytokine production after hemorrhage or endotoxemia [56] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that local administration of exogenous UA crystals recapitulates lung inflammation and repair. Local UA levels are also increased in patients with ALI, a syndrome characterized by the accumulation of neutrophils in the lung accompanied by the development of interstitial edema and an intense inflammatory response [23] . In fact, neutrophils rapidly infiltrate the pulmonary parenchyma after hypovolemic shock, intestinal ischemia/reperfusion, or endotoxin administration [8] , while the depletion of neutrophils reduces pulmonary edema and proinflammatory cytokine production after hemorrhage or endotoxemia [56] .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that both UA and MSU induce NET formation [10,37] , our findings, which indicated that these NET markedly increased the production of proinflammatory cytokine by the airway epithelial cells, suggest that NET could contribute to the exacerbation of lung inflammation, not only upon bleomycin administration but also in ALI. Recent studies reported increased UA levels in lung lavage fluid in a murine ventilator-induced lung injury (VILI) model [23] , and demonstrated that mechanical ventilation, together with LPS instillation, induced NET formation [57] . In this murine model, mechanical ventilation plus LPS was associated with increased airway levels of HMGB-1 and IL-1β, and a tendency to increase the CCL2/MCP-1 and IL-6 concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The translational relevance of NLR research is most evident in the novel therapeutic targets it has identified. Caspase-1, IL-1b, and IL-1 receptor antagonists, and the uric acid inhibitors, uricase and allopurinol, have been tested in animal models with varied success in combating deleterious NLR-mediated inflammation (57)(58)(59)(60). The next logical step for NLR research may incorporate environmental stressors (i.e., CS, ventilator support), with bacterial challenge, thus enhancing our understanding of NLRmediated antibacterial immunity within a framework relevant to human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is a potent product of catabolism that can act synergistically through the NLRP3 pathway in patients with acute lung injury. In this line, Kuipers et al 41 showed that pretreatment with allopurinol, which blocks uric acid synthesis by inhibiting the enzyme xanthine oxidoreductase, or uricase, which oxidizes uric acid into allantoin and water, did not reduce pulmonary neutrophil influx or pulmonary and plasma cytokine levels. Although both treatment strategies attenuated the lung wet/dry ratio, only allopurinol reduced total protein and IgM levels in BALF and was associated with a clear trend toward lower lung edema scores on histopathology.…”
Section: Endothelial Cellsmentioning
confidence: 99%